Customer satisfaction and switching behavior in Saudi Islamic banks: an exploratory study - Abduh, Muhamad; Altwijry, Othman Ibrahim (IIUM Institute of Islamic Banking and Finance, 2013)
Investigating Islamic banks customer satisfaction and switching behaviour is imperative for the Islamic banking industry because it could assist in explaining the level of relationship between Islamic banks and their customers. Accordingly, the present study is aimed at examining customer satisfaction and switching behaviour of Islamic banks’ customers for the case of Saudi Arabia. Data for this study is obtained through survey method that involves the distribution of questionnaire to about 216 Islamic banks’ customers in Saudi Arabia. Importance and performance analysis (IPA) method is employed to achieve the objective of this study. The finding of this study indicated that, internet banking, shariah compliance, confidentiality, bank’s type, accuracy of bank statement, new technology adoption, and front-line friendliness dimensions fall under the quadrant of “keep up the good work” with high level of performance and importance. In contrast, the attributes that are located in quadrant called “concentrate here” are ATM location, clarity in giving explanation, promptness in giving response, staff understanding on Islamic contracts, staff handling complaints and parking area.